Implementasi Konsep Halalan Thayyiban pada Rumah Makan Wong Solo Kota Palangka Raya - Satria, Ahmad Dhea; Syarifuddin, Syarifuddin (AL-QARDH, 2021)
This article tries to look at the phenomenon of development, A business that is required to have sensitivity to any changes that occur and put orientation to consumer satisfaction. Moreover, in Indonesia, which is majority Muslim, businesses are faced with sensitivity to halal food. This method of writing uses a qualitative descriptive approach, which will be expected to be able to describe of implementing the concept of halalan thayyiban. the results showed a special strategy used to attract consumers to come buy Wong Solo restaurant products. Halalan thayyiban as a marketing strategy of course not only the writing is displayed but also to the practice of application, both for owners, employees, and to all consumers also halalan thayyiban must be on all aspects of human life. Consumer response to the application of halalan thayyiban concept received a positive response from consumers. Considering Wong Solo restaurant not only makes the concept of halalan thayyiban as a slogan to attract consumer interest, but also as a slogan in life.